Latin American theories in International Relations looks to Antarctica (and vice versa) - Lorenzo, Cristian A. (2020)
The Antarctic Treaty System is dealing with several threats, such as the impacts of climate change, pollution, biopiracy, biological invasions, the increasing footprint of human activity, and global power shifts. Within this context, it is worth reflecting on the contributions of social science theories to the comprehension of such contemporary dilemmas for Antarctic policy-makers. Assuming that knowledge production is always situated, this paper explores Latin American theories in International Relations (IR) on Antarctica. The results show their view about the role that Latin America plays in world politics, and concerning Antarctica, different views about the demands for the exploitation of resources, the question of sovereignty, the future of the White Continent, and the Antarctic Treaty System. This paper concludes with some remarks about the contribution of such theories to the comprehension of the politics of Antarctica and highlights how these theories are elaborated in the context of new Antarctic dilemmas.